Electrodeposition of quaternary alloys in the presence of magnetic field. - Ebadi, M.; Basirun, Wan Jefrey; Alias, Y.; Mahmoudian, M. (SpringerOpen, 2010)
ABSTRACT: Electrodeposition of Ni-Co-Fe-Zn alloys was done in a chloride ion solution with the presence and absence of a Permanent Parallel Magnetic Field (PPMF). The PPMF was applied parallel to the cathode surface. The deposition profile was monitored chronoamperometrically. It was found that the electrodeposition current was enhanced in the presence of PPMF (9 T) compared to without PPMF. The percentage of current enhancement (Gamma%) was increased in the presence of PPMF, with results of Gamma% = 11.9%, 16.7% and 18.5% at -1.1, -1.2 and -1.3 V respectively for a 2400 sec duration. In chronoamperometry, the Composition Reference Line (CRL) for Ni was around 57%, although the nobler metals (i.e. Ni, Co) showed anomalous behaviour in the presence of Zn and Fe. The anomalous behaviour of the Ni-Co-Fe-Zn electrodeposition was shown by the Energy Dispersive X-Ray (EDX) results. From Atomic Force Microscopy (AFM) measurements, it was found that the surface roughness of the Ni-Co-Fe-Zn alloy films decreased in the presence of a PPMF.